2021
DOI: 10.1002/fsn3.2643
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the antioxidant activity, phytochemicals, and cannabinoid compounds of Cannabis sativa by salicylic acid elicitor

Abstract: Cannabis sativa L., commonly known as marijuana, is an annual dioecious herb from eastern Asia belonging to the family Cannabaceae (Russo, 2007). Cannabis is a remarkable medicinal herb containing many valuable natural components such as cannabinoids, terpenes, phenolics, carotenoids, alkaloids, and amino acids (Andre et al., 2016;Elsohly, 2007). Cannabis has been used for medicinal purposes, for treating pain, spasms, asthma, insomnia, depression, and loss of appetite, in many cultures for hundreds of years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In another study, the methanolic extract of the seeds showed an average activity against DPPH with an inhibition value of 75% at 500 µL/mL [ 83 ]. According to these authors, this activity is probably due to the presence of polyphenols and cannabinoids, known for their strong antioxidant capacity [ 164 , 165 ]. Moreover, other seed metabolites, such as lignamides [ 156 ] and proteins [ 157 ], exhibited average antioxidant activities.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the methanolic extract of the seeds showed an average activity against DPPH with an inhibition value of 75% at 500 µL/mL [ 83 ]. According to these authors, this activity is probably due to the presence of polyphenols and cannabinoids, known for their strong antioxidant capacity [ 164 , 165 ]. Moreover, other seed metabolites, such as lignamides [ 156 ] and proteins [ 157 ], exhibited average antioxidant activities.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing body of evidence that demonstrates that cannabinoids are differentially affected by phytohormone signaling pathways ( Mansouri et al., 2009 ; Mansouri and Asrar, 2012 ; Jalai et al., 2019 ; Mirzamohammad et al., 2021 ; Apicella et al., 2022 ). For example, the exogenous application of SA in one study led to an increase in CBD and THC concentrations but in another led to only an increase in THC production and a decrease in CBD production ( Jalai et al., 2019 ; Mirzamohammad et al., 2021 ). Application of methyl jasmonate (MeJA) to Cannabis plants also led to increased cannabinoid production, specifically THC ( Apicella et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%